2023
DOI: 10.1136/archdischild-2022-325271
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and behavioural outcomes at 2 years in babies born during the COVID-19 pandemic: communication concerns in a pandemic birth cohort

Abstract: IntroductionThe CORAL (Impact of Corona Virus Pandemic on Allergic and Autoimmune Dysregulation in Infants Born During Lockdown) study reported a reduction in social communication milestones in 12-month-old infants born into the COVID-19 pandemic.AimsTo look at 24-month developmental and behavioural outcomes in the CORAL cohort.DesignThe CORAL study is a longitudinal prospective observational study of Irish infants born in the first 3 months of the pandemic. At 24 months of age, the Ages and Stages Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Shuffrey et al in 2022 reported that birth during the pandemic was associated with delayed development, independent of maternal SARS-CoV-2 infection status, among American children [ 15 ]. Similar findings have been reported for Canadian and Irish infants [ 16 , 17 ]. There is an overall dearth of global data regarding growth indicators (wasting, stunting and underweight) among pandemic-born children which can independently affect childhood development.…”
Section: Introductionsupporting
confidence: 90%
“…Shuffrey et al in 2022 reported that birth during the pandemic was associated with delayed development, independent of maternal SARS-CoV-2 infection status, among American children [ 15 ]. Similar findings have been reported for Canadian and Irish infants [ 16 , 17 ]. There is an overall dearth of global data regarding growth indicators (wasting, stunting and underweight) among pandemic-born children which can independently affect childhood development.…”
Section: Introductionsupporting
confidence: 90%
“…Prior studies with smaller sample sizes showed variable findings across developmental domains, with lower communication and personal-social ASQ scores during the pandemic compared with before the pandemic. [17][18][19]24 Fewer studies have found decreases in problem-solving, although one study 19 found both increases and decreases in problem-solving scores depending on child age. Communication, personal-social, and problem-solving skills are honed during interpersonal interactions and may therefore have been most undermined by parent or caregiver stress during lockdowns, childcare closures, and social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a cohort study of US children aged 0 to 4 years (n = 684, 87% from the Northeast or West regions) found that 8% to 15% had negative changes in developmental screening results from the prepandemic period to the intrapandemic period; boys had more than twice the odds of having negative changes in communication and personal-social domains compared with girls . A study in Ireland (n = 917) found lower communication scores but otherwise similar profiles of development and behavior among 24-month-olds in the intrapandemic period compared with a prepandemic cohort . To date, however, studies have largely focused on small samples, limited US geographical areas or regions, or settings outside the US .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CORAL Study is a longitudinal study of over 350 Irish infants born into the pandemic 4. We have previously demonstrated that CORAL infants had limited social circles and a reduction in social/communication skills relative to a historical cohort at 12 and 24 months of age 3 4. We used eye-tracking technology to determine where 18-month-old CORAL infants fixed their gaze when looking at unmasked and masked adults.…”
mentioning
confidence: 99%